ANALISIS PERAS KOMPETENSI DAN DISIPLIN TERHADAP KINERJA KARYAWAN PT. SANTOMIC CITRA BERSAMA CABANG SANGATTA - Muhammad Awaluddin; Muhammad Rizal (Tinta Nusantara 2018 Vol.1, 2023)
The aim of the research is to find out whether the role of competency influences employee performance at PT. Santomic Partners Together. Does Work Discipline Affect Employee Performance at PT. Santomic Mitra Bersama. The results of the multiple linear test above can be explained that from the multiple linear regression equation model above is as follows: Y = 5.767 + 0.152 X1 + 0.555 X2 + e. A constant value of 5.767 states that if Competency and Discipline are ignored or equal to zero, then Employee Performance is 5.767. The regression coefficient of Competency is 0.152. What this means is that for every increase in the Competency level by one point, Employee Performance will increase by 0.152. Likewise, if competency decreases by one point, employee performance will decrease by 0.152. The regression coefficient for Discipline is 0.555. What this means is that for every increase in the Discipline level by one point, Employee Performance will increase by 0.555. Vice versa, if 0.555 decreases by one point, employee performance will decrease by 0.555.